Autonomy-Supportive Teacher Behaviours and Their Impact on Student Attendance at University Level (Teaching and Learning Inquiry, 2025)
Previous research on the motivation types located along a self-determination continuum revealed that the autonomy in students’ motivation has a positive impact on getting favourable results and underlined the importance of autonomy-supportive environments. Given that teacher behaviour is addressed as one of the forms of autonomy-supportive environments, the present study aimed to understand the nature of teacher behaviours in a mass course where the students explained the teacher as the most important motivational drive for their attendance in lectures. To this end, 101 first-year students studying at the Faculty of Humanities and Social Sciences participated in semi-structured interviews. The content analysis of qualitative data showed that the students were motivated by the teachers’ structured guidance, promotion of active participation, and acknowledgement of their ideas. Most importantly, their responses showed that lively teaching performance with use of humour and changing the tone of voice were the most important factors influencing their attendance behaviour. The results indicated that attendance was autonomously motivated by not only teachers’ informative, interactive, and caring behaviours but also teaching performance with some desired characteristics for university level students.